Meningkatkan Hasil Belajar Lompat Jauh Gaya Jongkok Menggunakan Permainan Lompat (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study aims to determine that the use of learning the game jump in long jump squat style can improve student learning outcomes V class Kendalserut MI Nurul Iman. This study is Action Research (PTK), which consists of two cycles. The research was conducted in MI Nurul Iman Kendalserut with 40 students. Results of research using traditional two-cycle and four meeting showed in the first cycle of the average value of 76.06 by the end of class presentations learning completeness 67.5% in the category good. While the second cycle of the average value of 87.11 by the end of class presentations mastery learning that 95% fall into the categories very high. It can be concluded the use of the game to jump on learning style long jump squat can improve student learning outcomes both in the realm of psychomotor, effective, and cognitive.